2015
DOI: 10.1177/0972262915599473
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Coping Styles among Doctors: Role of Demographic and Environment Variables

Abstract: Stress has been regarded as an occupational hazard since mid-1950s. In fact, occupational stress has been cited as a significant health problem among most of the occupational groups. Numerous studies have explored work stress among health care personnel in many countries. This study is an attempt to examine the nature and levels of role stress experienced by doctors in government hospitals across gender, experience, specialization and geographical areas in India. An attempt has also been made to explore the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…This indicates that while experience is beneficial the lowest impact of CIs is on younger workers. This is in contrast with prior research which has found younger doctors to be more likely to suffer from symptoms of stress and depression, although in that profession the reasons sometimes have to do with age-related differences in working conditions (Rashid and Talib 2015).…”
Section: Resultscontrasting
confidence: 94%
“…This indicates that while experience is beneficial the lowest impact of CIs is on younger workers. This is in contrast with prior research which has found younger doctors to be more likely to suffer from symptoms of stress and depression, although in that profession the reasons sometimes have to do with age-related differences in working conditions (Rashid and Talib 2015).…”
Section: Resultscontrasting
confidence: 94%
“…Work and family life are the two most important domains in a person's life. Lack of balance between the two can lead to adverse consequences, such as psychological distress, 37,38 low morale, harm to well-being, and so forth. 39 According to the two-factor theory, family life plays a major role in personal life, which is a hygiene factor leading to job dissatisfaction.…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%
“…Unsurprisingly, physicians do not invariably react to all the different stressors in hospitals, with some physicians developing more psychological symptoms than others, [10,11] indicating an association between the stress response to a stressor (ie, perceived stress) and psychological distress. Moreover, this association has been typically modest in Chinese physicians, [12,13] suggesting that psychological distress is not solely the results of stress reactions, but is also determined to a large extent by individual dispositions, [14,15] coping styles, and other personal and social resources.…”
Section: Introductionmentioning
confidence: 99%